Raziskave v marketingu - Iršič, Matjaž; Milfelner, Borut (2025)
Marketing Research. The monograph thoroughly outlines the phases of the marketing research process, ranging from problem identification to data collection, analysis, and report design. It details various methods, including structured and unstructured surveys, observation techniques, panel research, and others. The importance of maintaining high-quality research is emphasized, which necessitates coordinated collaboration between management and marketing researchers. The text also discusses sampling, highlighting how researchers must balance data accuracy with cost-effectiveness. It distinguishes between primary and secondary data. Moreover, the monograph focuses on data collection methods essential for understanding consumer behavior and market dynamics. Additionally it emphasizes relevant interpretation of data taht is crucial for effective decision-making, and the final phase of the research process which includes preparing reports and implementing findings. It provides guidelines for preventing errors and advocates for a relevant approach to marketing research.
Keywords: primary and secondary data; sample design; survey; observation; data analysis; research project plan